microRNAs-based Predictor Factor in Patients with Migraine-ischemic Stroke - Gallelli, Luca; Siniscalchi, Antonio; Carotenuto, Marco; C. Caroleo, Maria; Cione, Erika; Guidetti, Vincenzo (MicroRNA, 2017)
Among the clinical spectrum of neurological diseases, migraine is often associated with cerebro-vasculopathy. Impairment of neuroimmune mediators in the central nervous system has been recognized in the pathophysiology of migraine-related stroke. Although genetic correlation was found in patients with migraine-related stroke, the epidemiology of this disease indicates a need in biomarker searching discovery and validation. In this view, small molecule, called microRNAs (miRNAs), able to regulate immune and neuronal processes has been reported in patients with migraine and ischemic stroke and unambiguous miRNAs related to these diseases could be established as new molecular indicator of precocity for clinical and/or pharmacological intervention. Therefore, further exploration of this area is necessary, as greater understanding of these biomarkers could reveal the common mechanisms involved in the pathophysiology of migraine in patients with cerebral infarct.
Keywords: neurological diseases